Development and validation of a symptom‐based severity score for haemorrhoidal disease: the Sodergren score. (July 2015) - Pucher, P. H.; Qurashi, M.; Howell, A.‐M.; Faiz, O.; Ziprin, P.; Darzi, A.; Sodergren, M. H.
Abstract Aim One major obstacle in assessing the efficacy of treatment of haemorrhoids and the comparison of trials has been the lack of a standardized, validated symptom severity score. This study aimed to develop an objective, validated symptom‐based score of severity for haemorrhoids that can be used to compare treatments, monitor disease and assist in surgical decisions. Method A symptom and quality‐of‐life questionnaire was developed from the literature in conjunction with expert surgical opinion. The questionnaire was circulated to patients with confirmed haemorrhoids. A statistical model was used to derive a weighted score of symptoms most affecting patients' quality of life. Patients who were offered operative treatment were independently judged by specialists to have more severe symptoms, with further validation of the scoring system against treatment. Results Forty‐five patients were included in final validation analysis, of whom 44 (98%) reported multiple symptoms, the most common being rectal bleeding. Patient‐reported effects on quality of life were 47.5 ± 36.3 (1–100 visual analogue scale). Calculated symptom severity scores were used to compare patients receiving operative or ambulatory care, with significant difference in the scores (7.7 ± 3.9 vs 2.8 ± 3.5, P = 0.002) and a receiver operating characteristic area under the curve of 0.842. Conclusion A novel validated score for the assessment of haemorrhoidal disease adopting a standardized global score for symptom severity may have important implications in future for research, assessment and the management of this common pathology.